Orientação geográfica de estufas de polietileno e potenciais de água no solo no cultivo do melão rendilhado híbrido 'nero' - Braga, Marcos Brandão [UNESP]; Duenhas, Luiza Helena; de Souza, Cláudio Márcio Pereira; Klar, Antonio Evaldo [UNESP] (My University, 2006)
This study aimed to verify the effects of four different minimum soil watler potentials (-30, -40, -50 e -70 kPa) and two different plastic tunnel positions (North-South and East-West) on net melon yield. The results showed that in the East-West position the yield and fruit weight were higher than in the North-South position. The highest yields of melon crop were obtained from -30 kPa. to -40 kPa minimum soil water potential.
Plastic tunnel geographic orientation and soil water potential on irrigation management of net melon crop
Keywords: Cucumis melo reticulatus; Plastic tunnel; Soil water potential; Crops; Irrigation; Management; Soil testing; Tunnels; crop; irrigation system; soil water potential; tunnel; Cucumis; Cucumis melo